2014
DOI: 10.1155/2014/976347
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of a 23F Serotype Strain ofStreptococcus pneumoniaeto Cigarette Smoke Condensate Is Associated with Selective Upregulation of Genes Encoding the Two-Component Regulatory System 11 (TCS11)

Abstract: Alterations in whole genome expression profiles following exposure of the pneumococcus (strain 172, serotype 23F) to cigarette smoke condensate (160 μg/mL) for 15 and 60 min have been determined using the TIGR4 DNA microarray chip. Exposure to CSC resulted in the significant (P < 0.014–0.0006) upregulation of the genes encoding the two-component regulatory system 11 (TCS11), consisting of the sensor kinase, hk11, and its cognate response regulator, rr11, in the setting of increased biofilm formation. These eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 20 publications
8
40
4
Order By: Relevance
“…Notably, we did not observe upregulation of genes encoding TCS11 (SP_2000/SP_2001) in CSE-TIGR4 or in EVE +NIC -TIGR4 (Table 1). These results contradict previous observations that CS exposure upregulates transcription of TCS11 genes in pneumococcal serotypes 19F and 23F indicating the strain-dependent nature of these effects [18, 19]. Both CSE-TIGR4 and EVE +NIC -TIGR4 also exhibited altered expression of genes involved in carbon uptake and metabolism (phosphotranferase systems/PTS), pneumococcal stress response (Clp proteases, hrcA /SP_0515) and transcriptional regulators ( mgrA /SP_1800, marR /SP_1863, merR /SP_1856) and (Table 2).…”
Section: Resultscontrasting
confidence: 98%
See 4 more Smart Citations
“…Notably, we did not observe upregulation of genes encoding TCS11 (SP_2000/SP_2001) in CSE-TIGR4 or in EVE +NIC -TIGR4 (Table 1). These results contradict previous observations that CS exposure upregulates transcription of TCS11 genes in pneumococcal serotypes 19F and 23F indicating the strain-dependent nature of these effects [18, 19]. Both CSE-TIGR4 and EVE +NIC -TIGR4 also exhibited altered expression of genes involved in carbon uptake and metabolism (phosphotranferase systems/PTS), pneumococcal stress response (Clp proteases, hrcA /SP_0515) and transcriptional regulators ( mgrA /SP_1800, marR /SP_1863, merR /SP_1856) and (Table 2).…”
Section: Resultscontrasting
confidence: 98%
“…Compared to previous studies analyzing the effects of CS exposure on the pneumococcal transcriptome, the main discrepancy was observed in the expression genes encoding TCS11. Previous studies have reported that exposure to CS induces upregulation of TCS11 (SP_2000, SP_2001) expression in two different pneumococcal strains (serotypes 19F and 23F) and that TCS11 activity plays a role in pneumococcal biofilm formation but not in virulence in a mouse model [18, 19, 47]. However, we did not detect significant changes in the expression of TCS11 genes in any of our treatment groups.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations